Does Escrow Really Protect Consumers? : An Islamic Law Critique of Marketplace Transactions in Indonesia - Virya Suprayogi Yusuf; Maskun Maskun; Judhariksawan Judhariksawan; M. Arfin Hamid; Supriadi Supriadi; Muh Mutawalli Mukhlis (Justicia Islamica, 2026)
This article examines whether escrow (rekening bersama) genuinely protects consumers in Indonesian e-commerce, particularly in marketplace-based and off-platform social commerce transactions where fraud risks remain high. The study positions escrow not merely as a technical payment feature, but as a legally significant intermediary arrangement that structures duties, allocates liability, and enables evidentiary reliability and consumer remedies. Employing doctrinal legal research, the article operationally analyses statutes and implementing regulations related to electronic transactions, consumer protection, and electronic commerce (PMSE), while also providing a conceptual analysis of intermediary responsibility. Legal materials are systematically mapped to core escrow safeguards, including conditional fund release, verification, record integrity, and dispute handling, followed by interpretive analysis to identify regulatory gaps. The findings demonstrate that Indonesian law implicitly recognises escrow functions but lacks explicit governance standards, resulting in accountability and enforcement flaws. To address this, the article proposes a doctrinal–institutional escrow governance framework that outlines minimum operational safeguards, allocates responsibility for key failure scenarios, and provides implementation tools in the form of a safeguards checklist and liability map. An Islamic law critique, grounded in the principles of amanah and gharār reduction, further evaluates the fairness and risk containment of escrow practices. The study contributes a legally operational framework to strengthen ex ante consumer protection, enhance institutional trust, and guide regulatory standard-setting and platform compliance.